Clinical predictors of treatment response towards exposure therapy in virtuo in spider phobia: A machine learning and external cross-validation approach. (October 2021) - Leehr, Elisabeth J.; Roesmann, Kati; Böhnlein, Joscha; Dannlowski, Udo; Gathmann, Bettina; Herrmann, Martin J.; Junghöfer, Markus; Schwarzmeier, Hanna; Seeger, Fabian R.; Siminski, Niklas; Straube, Thomas; Lueken, Ulrike; et al.
Highlights: One-session VRET is a highly effective treatment for SP with large effect sizes. Individual short-term symptom reductions can be predicted above chance. Whereas, long-term outcome prediction was not significant. Between-site predictions of symptom reduction was not possible. Clinical utility of sociodemographic and clinical predictors alone is limited. Abstract: While being highly effective on average, exposure-based treatments are not equally effective in all patients. The a priori identification of patients with a poor prognosis may enable the application of more personalized psychotherapeutic interventions. We aimed at identifying sociodemographic and clinical pre-treatment predictors for treatment response in spider phobia (SP). N = 174 patients with SP underwent a highly standardized virtual reality exposure therapy (VRET) at two independent sites. Analyses on group-level were used to test the efficacy. We applied a state-of-the-art machine learning protocol (Random Forests) to evaluate the predictive utility of clinical and sociodemographic predictors for a priori identification of individual treatment response assessed directly after treatment and at 6-month follow-up. The reliability and generalizability of predictive models was tested via external cross-validation. Our study shows that one session of VRET is highly effective on a group-level and is among the first to reveal long-term stability of this treatment effect. Individual short-term symptom reductions could be predicted above chance, but accuracies dropped to non-significance in our between-site prediction and for predictions of long-term outcomes. With performance metrics hardly exceeding chance level and the lack of generalizability in the employed between-site replication approach, our study suggests limited clinical utility of clinical and sociodemographic predictors. Predictive models including multimodal predictors may be more promising.